The Impact of Digital Information Overload on the Financial Performance Efficiency of Micro-Entrepreneurs in the Social Media Era - Wibisono, Gunawan; Qosidah, Nanik (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2024)
The increasing use of social media in micro-enterprise activities has expanded access to business information while simultaneously creating digital information overload that may affect the quality of financial decision-making. This study aims to examine the effect of digital information overload on the financial performance efficiency of micro-entrepreneurs. A mixed-method approach with an explanatory sequential design was employed, involving 100 respondents for quantitative analysis using a five-point Likert-scale questionnaire and 10 informants for in-depth interviews conducted in 2025. Quantitative data were analyzed using simple linear regression, while qualitative data were examined through thematic analysis to enrich the interpretation of statistical findings. The results indicate that digital information overload significantly influences financial performance efficiency, particularly through information intensity, complexity, and processing difficulties that affect decision accuracy and cost management. This study contributes to the understanding of financial decision-making behavior in the digital era and provides practical implications for micro-entrepreneurs to manage information flows more selectively and strategically in order to enhance financial performance.